TEACHERS' OBSTACLES IN IMPLEMENTING THE INDEPENDENT CURRICULUM IN SCIENCE AND SCIENCE LESSONS AT SD NEGERI 1 LAMBHEU - Fitriani, Fitriani; Husin, M.; Fauzi, Fauzi (Universitas Syiah Kuala, 2025)
In implementing the Independent Curriculum, there are times when the role of education will experience obstacles in the implementation process. An obstacle is something that contributes to difficulties in the learning and learning process. This research seeks to reveal what obstacles teachers face in implementing the Independent Curriculum in Social Sciences Learning at SD Negeri 1 Lambheu. The aim of this research is to describe teachers' obstacles in implementing the independent curriculum in science and science learning. The approach used in this research is qualitative and descriptive research type. The subjects in this research were class IVa, IVb and V teachers. Data collection was carried out by observation, interviews and documentation. The data analysis techniques are carried out by data reduction, data presentation and drawing conclusions. The results of this research show that from observation and interview data teachers are still having problems in implementing the independent curriculum in science and science learning at SD Negeri I Lambheu. The teacher's obstacles are in planning, implementing and assessing learning. Due to lack of training and experience, teachers are hampered in compiling teaching modules, such as incomplete teaching module components, such as not including ATP, inappropriate learning objectives, meaningful understanding, as well as teachers having difficulty in determining methods, models, media, not utilizing technology, no LKPD, reading materials and the learning process are not yet as expected by the independent curriculum, teachers are limited in obtaining references, lack of tools and materials, material coverage is too broad and determines assessments that are in accordance with learning objectives. Based on the results of data analysis, it can be concluded, namely: The ability to carry out learning using the Independent Curriculum is in the quite good category. However, teachers experienced several obstacles in implementing the Independent Curriculum at SD Negeri 1 Lambheu